Proof of principle: the adaptive geometry of social foragers. (September 2016) - Dostie, Marcus J.; Lusseau, David; Bonnell, Tyler; Clarke, Parry M.R.; Chaplin, George; Kienzle, Stefan; Barrett, Louise; Henzi, S. Peter
Abstract : The spatial configuration of a group of animals should reflect the ability of its members to respond to environmental contingencies. Under predation risk, the optimal position for an individual in a stationary group is at the group's centre. The resulting group geometry is circular, with individual placement determined by competitive ability. Where it compromises efficient foraging, a long-standing question has been whether this topology can deform adaptively in response to the local distribution of resources. Here we show that the shape described by a group of foraging chacma baboons, Papio hamadryas ursinus, changes in response to habitat structure and that this promotes foraging efficiency while conserving the predation-risk-related distribution of group members. Adult baboons improve unimpeded access to the small, dispersed food items found in grassland by adjusting both their interindividual distances and their relative positions along the line of movement in order to forage in rank formation. Dominant animals occupy the centre of the group and do so regardless of its geometry. Our results demonstrate that spatially explicit data can address emergent group level properties directly. This global approach complements analyses of individual action and can help direct the search for potential local rules of interaction. Highlights: The geometry of a foraging baboon group responds adaptively to resource dispersion. The placement of individuals conforms to the expectations of a selfish herd. Global analyses can direct enquiries into the rules regulating individual movement.